Opportunity to apply international tax arbitrage by micro, small and medium sized enterprises in order to optimise tax-related cost of car use (Economic and Political Thought, 2019)
The article is aimed at evaluating international tax arbitrage applicationto optimise tax costs of using cars for business purposes by micro, small andmedium-sized (MMSE) enterprises. The main part of the work is devotedto analysing economic and fiscal aspects of tax liabilities connected withregistering cars in a related business entity operating in the Czech Republic.The evaluation of the issue is preceded by a presentation of an internationaltax arbitrage definition, a description of macroeconomic conditions forpurchasing cars in Poland and an overview of the evolution of current andforthcoming fiscal regulations influencing conditions for using cars by domesticand foreign MMSE firms.
Keywords: international tax arbitrage, tax optimisation, tax conditions for using cars for business purposes